2016
DOI: 10.1002/wps.20293
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement after sibling death: a population‐based longitudinal case‐control study

Abstract: The objective of this study was to examine mental disorders and treatment use among bereaved siblings in the general population. Siblings (N57243) of all deceased children in the population of Manitoba, Canada who died between 1984 and 2009 were matched 1:3 to control siblings (N521,729) who did not have a sibling die in the study period. Generalized estimating equations were used to compare the two sibling groups in the two years before and after the index child's death on physician-diagnosed mental disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…Although bereavement is a natural life event, it is often followed by emotional suffering and adjustment challenges. Studies have shown an association between the loss of a loved one and a range of mental health complications, particularly depression and post‐traumatic stress disorder.…”
mentioning
confidence: 99%
“…Although bereavement is a natural life event, it is often followed by emotional suffering and adjustment challenges. Studies have shown an association between the loss of a loved one and a range of mental health complications, particularly depression and post‐traumatic stress disorder.…”
mentioning
confidence: 99%
“…[3][4][5] The relation between siblings is perhaps the most significant and lasting relation that if you live The child, who loses a brother during his or her childhood or adolescence, is naturally the family member who lives the most time with this loss. 2,[6][7]30 It is explained that in the situation where there is a child / adolescent with a complex chronic life-limiting illness, which may even be prolonged for some time and which is understandably the center of care for the whole family, the brother resents for lack of equal attention, 9,24 loses visibility within his own family, 10,28 sometimes receiving messages from close friends to restrain his hurt, to be strong by his parents. These behaviors lead the child to feel that the pain of their loss is discredited, devalued, misunderstood, ignored.…”
Section: • Experience the Loss Of A Brother -Pathsmentioning
confidence: 99%
“…Some studies 8,14,21,28 show that, in the long run, surviving siblings may still feel guilty, high vulnerability, anxiety, fear of dying prematurely, excessive concern with others, especially with regard to their own children. 18 It is evidenced, through the results of investigations, 6,30 fraternal grieving as a period of vulnerability and an important focus of attention for the accompaniment of the people who live this experience. They also underline the relevance to public awareness of the importance of developing support structures for bereaved people.…”
Section: • Integrating Loss In Lifementioning
confidence: 99%
“…Siblings of children with cancer might experience this lack of attention already during the sibling's cancer illness, leading to feelings of loneliness, jealousy, anger, and guilt . Bereaved siblings showed prolonged grief; higher rates of mental disorders, ie, depression, anxiety, and substance use disorder; and higher rates of suicide attempts compared with nonbereaved siblings . After a major life crisis, like the death of a family member, individuals might also experience a positive change, as indicated by reports of personal or posttraumatic growth (PTG) after parental or sibling loss …”
Section: Introductionmentioning
confidence: 99%